Toxicological aspects of interesterified fat: Brain damages in rats. (5th July 2017) - D'avila, Lívia Ferraz; Dias, Verônica Tironi; Vey, Luciana Taschetto; Milanesi, Laura Hautrive; Roversi, Karine; Emanuelli, Tatiana; Bürger, Marilise Escobar; Trevizol, Fabíola; Maurer, H. Luana
Graphical abstract: Highlights: In recent years interesterified fat (IF) has replaced trans fat in processed foods. Dietary fatty acids are easily incorporated in neural brain membranes. IF in early stages of life reduces hippocampal DHA incorporation, impairing memory. IF in early stages of life favors oxidative damages development in hippocampus. IF from gestation until adulthood decreases hippocampal BDNF and TrKB levels. Abstract: In recent years, interesterified fat (IF) has been used to replace hydrogenated vegetable fat (HVF), rich in trans isomers, being found in processed foods. Studies involving IF have shown deleterious influences on the metabolic system, similarly to HVF, whereas no studies regarding its influence on the central nervous system (CNS) were performed. Rats from first generation born and maintained under supplementation (3 g/Kg, p.o.) of soybean-oil or IF until adulthood were assessed on memory, biochemical and molecular markers in the hippocampus. IF group showed higher saturated fatty acids and linoleic acid and lower docosahexaenoic acid incorporation in the hippocampus. In addition, IF supplementation impaired short and long-term memory, which were related to increased reactive species generation and protein carbonyl levels, decreased catalase activity, BDNF and TrkB levels in the hippocampus. To the best of our knowledge, this is the first study to show that lifelong IF consumption may be related to brain oxidative damage, memory impairments and neurotrophins modifications, which collectively may be present indifferent neurological disorders. In fact, the use of IF in foods was intended to avoid damage from HVF consumption; however this substitute should be urgently reviewed, since this fat can be as harmful as trans fat.